Utilization of enzyme hydrolysis from Shrimp Head in improve the quality catfish - Untari, Untari; Hukom, Evi Hudriyah; Permata, Reni (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2022)
Protein is one of the most important components that can support the growth and development of catfish. The price of feed with high protein content which is relatively expensive is a big problem in the catfish farming process. On the one hand, there is shrimp head waste which is a source of protein with a protein content of 42.16% - 49.8% which has not been utilized and is disposed of as waste. Through this research, the shrimp head waste was carried out by an enzyme hydrolysis process to produce shrimp soluble extract (SSE) using a protease enzyme. The SSE that has been produced is then given to catfish aged 14 days to support the addition of protein sources for the growth of catfish. During the 1 month trial, there was a significant difference in results in the treatment catfish with the addition of 2% SSE compared to the control catfish. The addition of SSE gave a very good effect on the weight of catfish which was randomly distributed in a tank containing 50 catfish with an average initial weight of 0.6-0.8 grams. The provision of SSE was carried out simultaneously with the provision of standard fish feed, namely 3 times a day. The increase in catfish weight after being treated was about 2 grams/week. This indicates that SSE can increase the growth of catfish and can be used as an alternative supplement in the future because in addition to reducing the level of pollution due to catfish waste, it can also be a new discovery in the field of fisheries.